Managing interpersonal conflict - Donohue, William A. (William Anthony), 1949-; Kolt, Robert; Sage eBooks (Newbury Park, Calif. : SAGE, 1992)
This title explores the process of interpersonal conflict - from the initial decision as to whether or not to confront differences through to how to plan the actual confrontation. It deals extensively with negotiation and, where negotiation proves unsuccessful, with third-party dispute resolution.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Interpersonal conflict; Negotiation; Conflict management; Electronic books